Circular Economy and Maqasid al-Shari’ah: A Conceptual Framework for Islamic Economic Reform - Afandi, M. Yazid; Rahma, Nadia (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2025)
The global environmental crisis, natural resource degradation, and growing economic inequality have intensified the demand for a development paradigm that is not only economically efficient but also socially and ecologically equitable. The circular economy has emerged as an alternative framework that emphasizes sustainable product life cycles, waste reduction, and resource optimization. From an Islamic perspective, this concept aligns significantly with the maqāṣid al-sharī‘ah—the overarching objectives of Islamic law aimed at preserving religion, life, intellect, progeny, and wealth. This article seeks to identify and analyze the relationship between the principles of the circular economy and the five dimensions of maqāṣid al-sharī‘ah. Employing a qualitative content analysis (QCA) approach, this study demonstrates that the principles of reuse, recycling, and remanufacturing within the circular economy correspond closely with efforts to safeguard the values of human life (faith and human rights—ḥifẓ al-dīn and ḥifẓ al-nafs), ensure human safety and intellectual integrity (ḥifẓ al-nafs and ḥifẓ al-‘aql), preserve societal continuity (ḥifẓ al-nasl), and protect both physical environments and material wealth (ḥifẓ al-māl and ḥifẓ al-bī’ah). Accordingly, the circular economy may be adopted as a model of development that is not only environmentally friendly but also deeply aligned with the holistic ethical values of Islam. This study contributes to the discourse on contemporary Islamic economics by offering a normative and practical framework that is responsive to current global challenges.